Dinamika Komunikasi Dan Sinergitas Multi-Stakeholder Dalam Optimalisasi Program Koperasi Desa Merah Putih - Is Susanti (STAI Bumi Silampari, 2026)
This research analyzes the dynamics of communication and multi-stakeholder synergy in optimizing the Merah Putih Village Cooperative Program in Bioa Sengok Village, Lebong Regency, Bengkulu. Launched through Presidential Instruction No. 9 of 2025, this program aims to establish 80,000 village cooperatives to strengthen the people's economy. The study focuses on the patterns of communication and synergy between the village government, village elites, and the community as the main stakeholders. Using a descriptive qualitative approach with a single case study, the research integrates Collaborative Governance Theory (Emerson & Nabatchi, 2015), Stakeholder Theory (Freeman, 2010), and Policy Network Theory (Rhodes & Marsh, 1992). Data were collected through in-depth interviews, field observations, document studies, and focus group discussions. The main findings show that communication patterns between stakeholders are still top-down and instructive, with significant information gaps. Vertical coordination is hampered by the unpreparedness of the village administration system, while horizontal coordination faces potential conflicts with BUMDes. Community participation is low due to a lack of socialization, even though mutual aid-based social capital remains strong. Supporting factors include the adaptive capacity of the village government, the existence of established BUMDes, strong social capital, district support, and local economic potential. Hindering factors include unclear regulations, limited human resources, weak cross-sector coordination, and funding uncertainty.